Using a phase-differential busbar protection for switchgears of power system facilities - Kulagin, D. O.; Fedosha, D. V.; Nitsenko, V. V.; Shevchenko, S. Yu.; Danylchenko, D. O. (Національний гірничий університет, 2019)
Purpose. To develop a concept for the implementation of a more advanced device designed for the busbar protection of power plants and substations which has advantages in technical operation over its traditional analogs by applying the phase-differential principle of this protection. Methodology. When developing the concept of implementation of phase-differential busbar protection, we used the method of comparative analysis, in particular, a qualitative analysis of the characteristics of busbar protection was carried out; difficulties encountered in the operation of traditional differential protection as well as advantages that can be obtained by introducing phase differential protection were considered in the work. Findings. Based on many years’ experience in the operation of differential current protection at power system facilities, the problematic issues of its operation are identified. We suggest using the phase-differential principle for busbar protection operation; its distinctive features are distinguished in comparison with traditional protections. The conditions for starting, tripping and returning of the phase-differential protection are determined, and there is suggested a method for determining the sensitivity of phase relay concerned to the angle. The phase characteristic of the protection is shown, which is the major operating characteristic which determines the width of the working zone and the blocking of this protection type. Originality. For the first time, use of phase-differential busbar protection, the principle of which is based solely on comparing the phases of the secondary currents of bays, connected to the common busbar system, has been suggested. At the same time, there is no provision for the use of any additional protection relays, which can provide a protection starting and use a different principle of operation from the phase-differential one. Practice value. The phase-differential busbar protection relay can be accepted into the technical operation in the power system facilities as an alternative option of using the traditional differential current protection. It has a number of advantages and allows solving existing problems of protection operation caused by increased requirements for current transformers in differential busbar protection circuits, necessity of tedious calculations of its, рабочих уставок, information redundancy and complexity of modern digital relays, which perform the function of phase-differential protection.

Мета. Розробити концепцію з реалізації більш досконалого пристрою, призначеного для релейного захисту збірних шин розподільчих установок електричних станцій і підстанцій, що матиме певні переваги в технічній експлуатації перед його традиційними аналогами, шляхом застосування диференційно-фазного принципу дії цього захисту. Методика. При розробці концепції з імплементації диференційно-фазного захисту шин застосовано метод порівняльного аналізу, а саме проведено якісний аналіз характеристик релейного захисту збірних шин, визначені труднощі, що виникають при експлуатації традиційних диференційних струмових захистів, і переваги, які можуть бути отримані при впровадженні диференційно-фазного захисту, наявність яких обумовлена його особливостями, розглянутими в роботі. Результати. На підставі багаторічного досвіду експлуатації диференційних струмових захистів на об’єктах електроенергетичної системи були встановлені проблемні питання їх експлуатації. Запропоноване використання диференційно-фазного принципу дії захисту шин, виділені його відмінні риси в порівнянні із традиційними захистами. Визначені умови пуску, спрацювання й повернення диференційно-фазного захисту шин, а також запропоновано спосіб визначення чутливості його фазного органу за кутом. Наведена фазна характеристика захисту, яка є його основною робочою характеристикою, що визначає ширину зони спрацювання та блокування захисту. Наукова новизна. Уперше запропоновано застосувати диференційно-фазний захист шин, принцип дії якого заснований виключно на порівнянні фаз вторинних струмів приєднань, підключених до спільної системи збірних шин. При цьому не передбачається застосування будь-яких додаткових пускових органів захисту, що виконані за відмінним принципом дії від диференційно-фазного. Практична значимість. Пристрій диференційно-фазного захисту шин може бути впроваджений у технічну експлуатацію на об’єктах електроенергетичної системи як альтернативний варіант застосуванню традиційних диференційних струмових захистів. Він має низку переваг і дозволяє вирішити існуючі проблеми експлуатації захистів, обумовлені підвищеними вимогами до вимірювальних трансформаторів струму в колах диференційного захисту шин, необхідністю виконання громіздких розрахунків його робочих уставок, інформаційною надлишковістю та складністю сучасних цифрових пристроїв, що виконують функцію диференційного захисту шин.
Застосування диференційно-фазного захисту шин розподільчих установок об`єктів електроенергетики
Keywords: phase-differential busbar protection; differential current protection; switchgear; busbar; relay protection; диференційно-фазний захист шин; диференційний струмовий захист шин; установка розподільча; шини збірні; захист релейний